La paradoja de la protección de los defensores de derechos humanos: entre la emancipación y las cadenas del desarrollo - Asier Tapia-Gutiérrez (Revista Iberoamericana de Estudios de Desarrollo)
In this work it is showed, taking as an example the growing wave of protection of human rights defenders, the contradictory relationship between development and human rights as an integrant part of that this discourse and the emancipatory possibilities through this tool for the defence of human dignity.